1988
DOI: 10.1007/bf01852318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on platelet thromboxane formation after ethanol withdrawal in chronic alcoholics: An in vitro study

Abstract: The effect of ethanol on the formation of platelet thromboxane B2 (TXB2), a stable metabolite of thromboxane A2 (TXA2) was studied in vitro in six chronic alcoholics, admitted for detoxification, and in six healthy volunteers. Immediately after cessation of heavy drinking platelet count and ADP-induced TXB2 formation were lower in alcoholics than in nonalcoholic volunteers (P less than 0.05). Ten days after withdrawal of ethanol platelet count increased, and skin bleeding time shortened (P less than 0.05). Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…In agreement with results of others (2,5,7,38,39), we found that platelet count increases upon withdrawal. Since ethanol suppresses thrombopoiesis (40), the increase in platelet count may be attributed to an alleviation of this suppression.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with results of others (2,5,7,38,39), we found that platelet count increases upon withdrawal. Since ethanol suppresses thrombopoiesis (40), the increase in platelet count may be attributed to an alleviation of this suppression.…”
Section: Discussionsupporting
confidence: 93%
“…Plasma tissue plasminogen activator (tPA) antigen was reported also to be increased in heavy drinkers, which is consistent with a decreased fibrinolytic activity 65 . The acute withdrawal of ethanol is known to have rebound effects, including the activation of platelets by normal agonists 66 ; therefore, while moderate alcohol consumption can be protective against cardiovascular disease partly through decreased fibrinogen levels, short-term binge drinking may have a hypofibrinolytic effect through increased PAI-1 levels and rebound platelet hyperaggregability 67 .…”
Section: Discussionmentioning
confidence: 99%